Using the ESID Model To Reduce Intimate Male Violence Against Women - Sullivan, Cris M. (American Journal of Community Psychology, 2003)
This paper describes how the Experimental Social Innovation and Dissemination (ESID) model was successfully used to reduce male violence against women in an intimate relationship. The women in the study who worked with advocates (the key feature of the program) were significantly less likely to be abused again compared to their counterparts in the control condition. They also reported a higher quality of life and fewer difficulties in obtaining community resources even 2 years after the short-term intervention. The advocacy provided consisted of five phases: assessment, implementation, monitoring, secondary implementation, and termination. Assessment collected important information on the client's needs and goals. This involved asking the women what they needed and by observing women's circumstances. In response to each unmet need identified, the advocate worked with the woman to access appropriate community resources. This was the implementation phase. The third phase involved monitoring the effectiveness of the intervention. The advocate and client assessed whether the resource had been obtained and whether it met the identified need. If it was not effective, advocates and clients initiated a secondary implementation to meet the client's needs more effectively. Termination of the intervention consisted of three components. First, advocates emphasized termination dates from the beginning of the intervention in order to prevent termination from surprising the client. Second, beginning about week seven of the 10-week intervention, advocates intensified their efforts to transfer the skills and knowledge the women had acquired throughout the course. Third, advocates left families with written “termination packets,” which contained lists of community resources, helpful tips for obtaining difficult-to-access resources, and useful telephone numbers. A total of 143 women participated in the experimental condition, and women in the control group were not contacted again until their next interview; they received services-as-usual. 30 references
Num Pages: 9
Keywords: Criminologie; Expérimentation; Innovation sociale; Réservé UdeM; Soutien social; États-Unis